2000
DOI: 10.1116/1.1324637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoothing on defect printability at extreme ultraviolet wavelengths

Abstract: Improvements in mask blank yield by the reduction in defects dramatically reduces the reticle cost of any lithography. Extreme ultraviolet lithography (EUVL) masks typically consist of a substrate coated with reflective multilayer (ML) materials (e.g., Mo and Si), followed by a sacrificial or “repair” layer (e.g., SiO2) and top absorber layer material (e.g., Cr or TaSiNx). Defects of the following two types exist: substrate and absorber defects. Substrate defects are generally below the absorber and buffer lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…We are also investigating other materials that might be capable of enhancing the defect smoothing approach. [23] More recently, a method for multilayer defect repair has been reported, and preliminary modeling and experimental results indicate the concept is feasible. [24] With the efforts in defect reduction during deposition in conjunction with the use of smoothing layers and methods of repairing buried defects, it seems possible that the industry need for defect free EUVL mask blank can be met.…”
Section: Defect Mitigationmentioning
confidence: 99%
“…We are also investigating other materials that might be capable of enhancing the defect smoothing approach. [23] More recently, a method for multilayer defect repair has been reported, and preliminary modeling and experimental results indicate the concept is feasible. [24] With the efforts in defect reduction during deposition in conjunction with the use of smoothing layers and methods of repairing buried defects, it seems possible that the industry need for defect free EUVL mask blank can be met.…”
Section: Defect Mitigationmentioning
confidence: 99%
“…Such EUV sources and corresponding beam steering optics are currently being developed with tremendous effort. [2][3][4][5][6][7][8][9][10][11][12][13] Besides semiconductor microlithography, there are also other applications of EUV radiation, which can strongly profit from the EUVL source and optics developments. For instance, Bonfigli et al demonstrated the generation of surfacenear color centers in LiF crystals positioned in the vicinity of a laser-produced EUV plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Phase defects would change in line width in the printed image. [1][2][3][4][5][6][7] It has been reported that a phase defect with a surface bump of 2 nm height and full width at half maximum (FWHM) of 60 nm, which is a critical size for printable defects, causes an unacceptable line width change of 20 %, to 35 nm line (140 nm on the masks). 2,4 It is very important to closely inspect and reduce the phase defects with a small height.…”
Section: Introductionmentioning
confidence: 99%
“…Near-normal incident deposition and ion-assisted deposition techniques have been evaluated as a smoothing technique for the mitigation of phase defects in the multilayer. 1,4,6,[8][9][10][11][12][13][14] Recently, repair techniques for the phase and amplitude defects have been developed using focused ion beams (FIB) and electron beams (EB). 4,14 The smoothing technique and the repairing technique, however, have not yet been sufficient investigated for cross sectional multilayer stack image.…”
Section: Introductionmentioning
confidence: 99%